Measuring the Potential of Unilateral CDM: A Pilot Study - Stefan Raubenheimer; Axel Michaelowa; Michael Jahn; Holger Liptow (Hamburg Institute of International Economics (HWWA), 2004)
The Clean Development Mechanism (CDM) was originally seen as an instrument with a bilateral character where an entity from an industrialised country invests in a project in a developing country (DC). Also, multilateral funds were envisaged that would bundle investments to spread project risks. The sluggish implementation of incentives for industrialised country companies to embark on CDM projects and low carbon prices led to a preference of just buying Certified Emission Reductions (CERs) instead of investing in projects. Thus a third option has gained prominence – the unilateral option where the project development is planned and financed within the DC. We propose that a project should be called ?pure unilateral? if it involves no foreign direct investment (FDI), only has the approval of the Designated National Authority (DNA) of the host country and sells its CERs after certification directly to an industrialised country. Unilateral projects can become attractive if the host country risk premium for foreign investors is high despite a high human, institutional and infrastructure capacity and domestic capital availability. Moreover, transaction costs can be reduced compared to foreign investments that have to overcome bureaucratic hurdles. On the other hand, technology transfer is likely to be lower, capacity building has to be done by the host country and all risks have to be carried by host country entities. The potential to carry out unilateral CDM projects strongly varies among DCs. Whereas several countries from Asia and Latin America might well be able to design projects autonomously, most of the Sub- Saharan countries rely on foreign support. International donors of capacity building grants should increasingly address those DCs that are not in the focus of foreign investors and support them in the design of projects.
Keywords: Q25; O13; 330; Clean Development Mechanism; unilateral; institutions; project participants; financing; risk premium; Clean Development Mechanism; Entwicklungsprojekt; Projektfinanzierung; Länderrisiko; Entwicklungsländer